Incidence and predictors of cardiogenic shock following surgical or transcatheter tricuspid valve intervention. Issue 5 (23rd January 2022) - Lawlor, Matthew K.; Hamid, Nadira; Kampaktsis, Polydoros; Ning, Yuming; Wang, Victoria; Akkoc, Deniz; Dershowitz, Lyle; Placheril, Elizabeth; Vahl, Torsten P.; Nazif, Tamim; Khalique, Omar; Ng, Vivian; et al.
Abstract: Objective: The objective of this study was to evaluate the incidence of and risk factors associated with cardiogenic shock (CS) following surgery versus transcatheter tricuspid valve intervention (TTVI) for tricuspid regurgitation (TR). Background: Surgical therapy for TR is associated with high rates of CS. Postprocedural shock has not been studied following TTVI. Methods: We performed a single‐center retrospective analysis of isolated tricuspid valve (TV) surgery or TTVI for TR. The primary outcome was postprocedural class D or E CS according to Society for Cardiovascular Angiography and Interventions (SCAI) CS classification scheme, and secondary outcome was in‐hospital mortality. Multivariable logistic regression modeling was performed for primary and secondary outcomes. Support vector machine analysis was performed for sensitivity analysis. Results: From 2008 to 2020, a total of 122 patients underwent isolated TV surgery ( n  = 58, 14 TV repair, and 44 TV replacement) or TTVI ( n  = 64, 36 TV repair, and 28 TV replacement). Surgical patients were significantly younger than TTVI patients (67.5 vs. 80 years, p  < 0.0001). Multivariable modeling revealed an association between the primary outcome and surgery (odds ratio [OR]: 8.75, 95% confidence interval [CI]: 2.83, 27.03, p  = 0.0002), as well as baseline central venous pressure (CVP, OR: 1.12, 95% CI: 1.02, 1.22, p  = 0.016). Additionally, class DE CS was independently associated with in‐hospital mortality (OR: 5.21, 1.35, 20.09, p  = 0.016). CVP and surgery were found to have highest importance indices in support vector machine analysis. Conclusion: In patients undergoing TV intervention for TR, surgery versus TTVI and elevated CVP are associated with advanced postprocedural CS. Patients developing advanced CS are at increased risk of in‐hospital mortality.